A cluster based approach for wormhole attack detection in wireless sensor networks - Shahryari, Maliheh; Reza Naji, Hamid Reza (Journal of Advanced Computer Science & Technology, 2015)
Due to the need of cooperation among nodes to relay packets, wireless sensor networks are very vulnerable to attacks in all layers of the network. One of these severe attacks is the wormhole attack. Detection of wormhole attack is hard, because it can be easily implemented by attacker without having knowledge of nodes in the network or it can be compromised by any legal node in the network. To date, the most of proposed protocols to defend against wormhole attacks are made by adopting synchronized clocks, directional antennas or strong assumptions in order to detect wormhole attacks.A method based on clustering is presented in this paper to detect this type of attacks. This method is implemented in static and mobile networks. The superiority of our protocol is that during the attack prevention or attack detection, the malicious nodes are detected and requires no additional hardware or complex calculations. Simulation results are perused with the NS-2 simulator and the protocol has been evaluated in terms of packet drop ratio, throughput, delay and energy consumption compared to a network without or under attack. Simulation results show that our protocol is practical and effective in improving resilience against wormhole attacks.